Escola Livre de Artes Arena da Cultura: building bridges between training and cultural inclusion of youth and adults (Cadernos de Sociomuseologia, 2020)
The article makes explicit and analyzes the participatory methodologies of exhibition curators in the context of the Escola Livre de Artes Arena da Cultura. It is possible to present reflections on the experience lived as a Teacher at that School, located in Belo Horizonte, capital of Minas Gerais (BH-MG), in the second semester of 2019. Initially I present the ELA-Arena guidelines, and then I bring bases and discussions around this work. In addition to conclusions, I intend that the article brings good examples of the possibilities of democratization and cultural accessibility that have occurred at the local level.Keywords: participatory methodologies; curatorship; cultural inclusion.